Clinical outcome of neonatal bacterial meningitis according to birth weight Evolução clínica da meningite bacteriana neonatal de acordo com o peso de nascimento - Vera Lúcia Jornada Krebs; Gleise Aparecida Moraes Costa (Arquivos de Neuro-Psiquiatria)
OBJECTIVE: To describe the clinical outcome and the complications of bacterial meningitis according to birth weight of out born neonates admitted in intensive care unit during an 11 year-period. METHOD: Eighty-seven newborns were studied. Thirty-four infants were low birth weight newborn and 53 presented birth weight > " 2500 g. The clinical data were obtained through the analysis of patients’ files. Fisher’s exact test, the c² and the Mann-Whitney test were applied. RESULTS: Neurological symptoms were more common in infants weighed > " 2500 g (p<0.05). Complications affected half of the cases in both groups. Complications affected half of the cases in both groups, with an overall mortality rate of 11.5%. CONCLUSION: The rate of complications was high in both groups, regardless of the birth weight. No association was observed between the occurrence of death and birth weight. Infants with positive CSF culture had a poorer prognosis. OBJETIVO: Descrever a evolução clínica e as complicações da meningite bacteriana de acordo com o peso de nascimento em recém-nascidos admitidos em unidade de terapia intensiva externa durante o período de 11 anos. MÉTODO: Foram estudados 87 neonatos, dos quais 34 foram recém-nascidos de baixo peso e 53 apresentaram peso > " 2500 g. Os dados clínicos foram obtidos por análise dos prontuários médicos. Foram realizados teste exato de Fisher, teste do c² e teste de Mann-Whitney. RESULTADOS: Os sintomas neurológicos foram mais comuns em neonatos com peso > " 2500 g (p<0,05 ). As complicações ocorreram na metade dos casos em ambos os grupos, com mortalidade global de 11.5%. CONCLUSÃO: A freqüência de complicações foi alta em ambos os grupos, independentemente do peso de nascimento. Não houve associação entre óbito e peso de nascimento. Os neonatos com cultura de líquor positiva apresentaram pior prognóstico.